Description of a new small‐sized Synodontis species (Siluriformes: Mochokidae) that is important for local subsistence fisheries in the middle Lufira (upper Congo River, DR Congo). Issue 5 (4th August 2019) - Kasongo Ilunga, Micheline; Abwe, Emmanuel; Decru, Eva; Chocha Manda, Auguste; Vreven, Emmanuel
Abstract: Synodontis denticulatus sp. nov. is an endemic from the middle Lufira Basin and its associated tributaries and lakes. The species shows close morphological resemblance to Synodontis greshoffi and Synodontis unicolor, which are widespread Congo Basin and Bangweulu‐Mweru endemic species, respectively. However, it differs from both S. greshoffi and S. unicolor by its non‐villous skin ( v . villous skin), strong and numerous serrations on the posterior margin of the dorsal spine ( v . weak and fewer serrations), weak and few serrations on the posterior margin of the pectoral spine ( v . strong and numerous serrations), relatively short maxillary barbels ( v . long) and its small maximum standard length (89.1 mm L S v . 148.0 and 190.7 mm L S respectively). A DNA barcoding study ( coI, mtDNA) revealed that S. denticulatus forms a distinct genetic clade with a genetic distance of 2.18% with S. greshoffi and 0.84% with S. unicolor . Synodontis denticulatus is caught regularly and abundantly as a by‐catch in the gillnet fisheries in the middle Lufira lakes. Owing to its small overall size and large bony head, the species has usually no real commercial value but is an important food fish for the fishermen's families.